2021
DOI: 10.15587/1729-4061.2021.227952
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Ni(OH)2, suitable for supercapacitor application, by the cold template homogeneous precipitation method

Abstract: α-Ni(OH)2 obtained by template homogeneous precipitation exhibits high electrochemical activity in supercapacitors. The main disadvantage is the high energy consumption for maintaining a high temperature during synthesis. To reduce energy consumption, it is proposed to lower the synthesis temperature. In the study, α-Ni(OH)2 was obtained by the method of cold template homogeneous precipitation using Culminal C8465 (0.5 %) as a template for 6 months at t=20–35 °С. The electrochemical characteristics of the samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 48 publications
(59 reference statements)
0
4
0
Order By: Relevance
“…The main disadvantage of template synthesis is the need to remove the template, which can block part of the active surface of the particles. The influence of the amount of residual template on the specific capacity of hydroxide was researched [163] . It was shown that the residual amount of the Culminal C8465 template in the hydroxide particle can play the role of an internal binder in the preparation of the active mass.…”
Section: Application Fields Of Nickel Hydroxides: Required Properties...mentioning
confidence: 99%
See 1 more Smart Citation
“…The main disadvantage of template synthesis is the need to remove the template, which can block part of the active surface of the particles. The influence of the amount of residual template on the specific capacity of hydroxide was researched [163] . It was shown that the residual amount of the Culminal C8465 template in the hydroxide particle can play the role of an internal binder in the preparation of the active mass.…”
Section: Application Fields Of Nickel Hydroxides: Required Properties...mentioning
confidence: 99%
“…The influence of the amount of residual template on the specific capacity of hydroxide was researched. [163] It was shown that the residual amount of the Culminal C8465 template in the hydroxide particle can play the role of an internal binder in the preparation of the active mass. This will allow the use of such nickel hydroxide for the manufacture of a binder-free electrode, reducing the cost due to the absence of rinsing of the hydroxide and the exclusion of the use of an external binder.…”
Section: Hybrid Supercapacitormentioning
confidence: 99%
“…In this case, a mixed PP-PVA matrix was formed. PVA was also successfully used to obtain nickel hydroxide (as a separate substance) by template electrochemical synthesis [49] and template homogeneous precipitation [50,51] (including low-and high-temperature ones [52]).…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…α-Ni(OH) 2 is stacked randomly along the axis (001) due to the presence of the anions between layers accompanied by water molecules, whereas the β-Ni(OH) 2 is perfectly stacked as hexagonal crystals. The morphological control for both morphologies of Ni(OH) 2 can be achieved by synthetic conditions as well as the incorporation of polymers or surfactants [ 16 ].…”
Section: Introductionmentioning
confidence: 99%